The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.2166/wst.2001.0493
|View full text |Cite
|
Sign up to set email alerts
|

The flow structure in the separation zone of a DAF pilot plant and the relation with bubble concentration

Abstract: Fluid dynamics is believed to be of crucial importance for the removal mechanism in Dissolved Air Flotation. The paper is a presentation of experimental studies on velocity and air-content profiles in a DAF pilot plant. The correlation between air content and flow patterns is discussed. Two flow structures are detected. A stratified flow structure is defined by a horizontal transport of the water in a upper, less-dense layer, and a lower, downwards-vertical transport in the lower, dense layer. Between the laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 2 publications
2
8
0
2
Order By: Relevance
“…By including the effect of bubble aggregation for the first time in a CFD model of DAF, the model was able to identify conditions under which stratified flow occurs, and to quantitatively predict the benefit of the stratified flow in terms of better bubble removal. The results of the model were in good agreement with the experimental measurements of Lundh et al (2001). The inclusion of only two phases (air and water), however, was a limitation in the model, as it could not be used to directly extrapolate the impact of the stratified flow on particle removaldwhich is the ultimate goal of DAF treatment.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…By including the effect of bubble aggregation for the first time in a CFD model of DAF, the model was able to identify conditions under which stratified flow occurs, and to quantitatively predict the benefit of the stratified flow in terms of better bubble removal. The results of the model were in good agreement with the experimental measurements of Lundh et al (2001). The inclusion of only two phases (air and water), however, was a limitation in the model, as it could not be used to directly extrapolate the impact of the stratified flow on particle removaldwhich is the ultimate goal of DAF treatment.…”
Section: Introductionsupporting
confidence: 64%
“…Table 1 e Particle removal efficiency for varying air fractions and bubble sizes. Loading rate 11.8 m/hr, particle size 10 mm, particle density 1100 kg/m 3 , particle volume fraction 0.0001. w a t e r r e s e a r c h 6 8 ( 2 0 1 5 ) 2 6 2 e2 7 2 form stratified flow (bubbles are needed to create stratified flow since the stratified flow is caused by flow density differences, as explained in Lundh et al (2001)). In general, therefore, an increase in bubble size and air fraction up to a certain point promotes stratification of the flow, whereas an increase beyond this bubble size and air fraction can lead to the quick removal of all of the bubbles from top of the tank, thereby preventing the formation of stratified flow in the separation zone.…”
Section: Numerical (Cfd) Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Edzwald et al (1999) reported that, as the loading rate increased, the bubble bed (blanket) went deeper, but the relationship between the bubble depth and removal efficiency was not addressed. Lundh et al (2001) tried to measure the bubble concentration in a pilot plant with a turbidity meter, but the exact bubble bed depth could not be measured.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda assim existem muitas lacunas a serem preenchidas, sendo consenso na indústria de água a necessidade de mais pesquisas para a otimização do processo de FAD, bem como obtenção de critérios confiáveis de projeto, aumento dos níveis de segurança e qualidade, aumento da eficiência na clarificação, diminuição do tempo de floculação e, ainda, redução dos custos de investimento e operação. Neste sentido, a falta de experiência e de pesquisas acerca das características hidrodinâmicas do processo é notável (LUNDH et. al., 2001).…”
Section: Introductionunclassified